Method and Algorithm for Processing Large Volume Images - O. N. Andreichuk; N. I. Listopad (Цифровая трансформация)
The article proposes a new method and an algorithm based on it for processing large-volume images. What is new in the implementation of image processing is the method of implementing program code using the App object. The novelty of the proposed method also lies in the algorithm for the specific implementation of filters for processing graphic elements. During development, various problematic situations were taken into account, such as using modern variable declaration syntax, using arrow functions, dividing code into smaller functions or class methods, adding comments to complex sections of code, checking for errors and exceptions, and following standards and guidelines by coding style. The implemented algorithm in the JavaScript programming language is an effective web application that uses the EaselJS library to work with graphics and has specific logic for working with graphic layers, drawing tools and user interaction, which ultimately made it possible to improve code performance compared to known solutions.